2005
DOI: 10.1111/j.1468-0106.2005.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of a Greater China Currency Union

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, if each economy faces idiosyncratic shocks, such common monetary policy cannot work well as stabilizing instruments and, hence, the cost of joining a currency union will be quite large. Following Ghosh and Wolf (1994) and Cheung and Yuen (2005), we have conducted a sensitivity study by employing an output loss function analysis to assess the costs of forming a currency union between the Greater China economies. 17 The empirical results (not reported but available upon request) indicate that the estimated output losses for the rest of the union members are sensitive to the choice of the leading country and the labour share used in the estimations.…”
Section: Dynamic Analysis Of Correlation In Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if each economy faces idiosyncratic shocks, such common monetary policy cannot work well as stabilizing instruments and, hence, the cost of joining a currency union will be quite large. Following Ghosh and Wolf (1994) and Cheung and Yuen (2005), we have conducted a sensitivity study by employing an output loss function analysis to assess the costs of forming a currency union between the Greater China economies. 17 The empirical results (not reported but available upon request) indicate that the estimated output losses for the rest of the union members are sensitive to the choice of the leading country and the labour share used in the estimations.…”
Section: Dynamic Analysis Of Correlation In Shocksmentioning
confidence: 99%
“…However, this approach does not necessarily reveal how the (a)symmetry in shocks has evolved over time especially when economic interdependence between the economies concerned has deepened substantially. Recently Cheung and Yuen (2005) employ the Johansen cointegration technique to assess the suitability of a Greater China currency union, and Sato and Zhang (2006) also adopt the technique to measure the extent of business cycle synchronization for the purpose of evaluating the feasibility of East Asian monetary union. In contrast, this paper applies the time-varying parameter estimation technique developed by Haldane and Hall (1991), Boone (1997) and Babetskii et al (2004) to measuring the time-varying correlation of the identified shocks and the convergence trend, and then conducts an output loss function analysis a la Ghosh and Wolf (1994) to empirically assess the costs of renouncing autonomous monetary policy instruments should a currency union be formed in this region.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have typically explored whether the countries in question meet some of the pre-conditions set in the theory of optimum currency area (see de Grauwe [8]). Recently, Cheung and Yuen [5] and Sato and…”
Section: Several Studies Have Examined the Feasibility Of Forming A Mmentioning
confidence: 99%
“…First, we apply the multivariate cointegration technique to the issue of an East Asian monetary union. Recently Cheung and Yuen [6] and Sato and Zhang [22] employ the cointegration technique to assess the integration issue, but Cheung and Yuen [6] focus only on the three Greater China economies (the Mainland, Hong Kong and Taiwan). Even though Sato and Zhang [22] investigate the whole East Asian economies, they employ a bivariate VAR of real output series for possible pairs of countries within a twocountry framework.…”
Section: Introductionmentioning
confidence: 99%
“…5 Second, we attempt to investigate 60 groups of countries to detect possible regional currency areas, which is far more comprehensive than the previous literature. 6 We include in this study Japan and the United States in addition to nine East Asian economies including three Asian NIEs (Korea, Taiwan and Hong Kong), ASEAN5 (Singapore, Malaysia, Indonesia, Thailand 1 In the ASEAN + 3 (China, Japan and Korea) Finance Ministers Meeting on 6 May 2000 at Chiang Mai, participating countries agreed to establish a regional financing arrangement to supplement the existing international facilities through the "Chiang Mai Initiative". The Initiative involves an expanded ASEAN Swap Arrangement that would include all ASEAN countries, and a network of bilateral swap and repurchase agreement facilities among ASEAN countries, China, Japan and the Republic of Korea.…”
Section: Introductionmentioning
confidence: 99%